2021
DOI: 10.12998/wjcc.v9.i3.528
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and potential mechanism of coronavirus disease 2019-associated liver injury

Abstract: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2, has posed a serious threat to global public health security. With the increase in the number of confirmed cases globally, the World Health Organization has declared the outbreak of COVID-19 an international public health emergency. Despite atypical pneumonia as the primary symptom, liver dysfunction has also been observed in many clinical cases and is associated with the mortality risk in patients with COVID-19, lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 82 publications
0
15
0
1
Order By: Relevance
“…*Significant between no LI and mild LI, # Significant between no LI and severe, and $ Significant between mild LI and severe LI based on linear mixed models ◂ Table 2 Performance metrics (AUCs) of the individual top predictors of (A) mild and severe liver injury and (B) severe injury only at different days prior to onset For combined models using all top variables shown, AUCs determination excluded AST due to its strong correlation with ALT Taken together, given the relative late onset of sLI, high rate of IMV, anticoagulant and steroid use in sLI, there was likely hepatotoxicity from COVID-19 therapies that include antiviral, antibacterial, steroids, anticoagulants, and immuno-modulatory drugs, amongst others. In particular, the disproportional host-immune responses (including inflammation) are known to cause liver injury in COVID-19 patients [11][12][13][14]35]. Alternative interpretations are possible and prospective studies are warranted.…”
Section: Potential Mechanisms Of Liver Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…*Significant between no LI and mild LI, # Significant between no LI and severe, and $ Significant between mild LI and severe LI based on linear mixed models ◂ Table 2 Performance metrics (AUCs) of the individual top predictors of (A) mild and severe liver injury and (B) severe injury only at different days prior to onset For combined models using all top variables shown, AUCs determination excluded AST due to its strong correlation with ALT Taken together, given the relative late onset of sLI, high rate of IMV, anticoagulant and steroid use in sLI, there was likely hepatotoxicity from COVID-19 therapies that include antiviral, antibacterial, steroids, anticoagulants, and immuno-modulatory drugs, amongst others. In particular, the disproportional host-immune responses (including inflammation) are known to cause liver injury in COVID-19 patients [11][12][13][14]35]. Alternative interpretations are possible and prospective studies are warranted.…”
Section: Potential Mechanisms Of Liver Injurymentioning
confidence: 99%
“…The effects of COVID-19 on the liver remain incompletely understood [3][4][5][6][7][8][9][10]. The liver could be damaged by direct viral infection, indirect host-immune responses (i.e., thrombosis, cytotropic and cytokine-mediated immune responses, amongst others) and/ or hepatotoxicity from COVID-19 therapies that include antiviral, antibacterial, and immuno-modulatory drugs, amongst others [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In one earlier study pertaining to extrapulmonary manifestations of COVID-19, it was noted that 14-53% of patients with COVID-19 had abnormally elevated levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) [4]. Additionally, the degree of enzyme elevation is associated with more severe cases of COVID-19 [4][5][6]. The exact mechanism of this liver injury in the context of COVID-19 infection is not completely understood, but a few factors have been postulated to play a role.…”
Section: Introductionmentioning
confidence: 99%
“…One mechanism is direct damage from viral replication within cells [5,7,8]. Based on prior studies of the coronavirus family, it has been demonstrated that the virus enters cells via the ACE2 receptor, which is expressed on multiple cells in the body including hepatocytes and bile duct epithelial cells [6,8]. Viral replication and release result in the rupture of cells, generating elevated liver enzymes in the serum [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation